(untitled) (KYAMC Journal, 2022)
Background: Irritable Bowel Syndrome (IBS) is a functional disorder. Invariably it is co-morbid with psychiatric disorder and is associated with psychosocial stressors. Objectives: To see the association of types of IBS with psychiatric disorders and to assess the association of psychosocial stressors. Materials and methods: It was descriptive, cross-sectional study carried out in the Department of Gastroenterology, Bangabandhu Sheikh Mujib Medical University, Dhaka from January 2014 to December 2014. Total 250 samples were included in this study those were diagnosed as IBS. Respondents were above 18 years of age of either sex. Sampling technique was consecutive. Results: The patients with psychiatric disorders among IBS patients were 86.4%. Maximum (35.2%) were IBS-D followed by 32.8% IBS-C and 32% IBS-M. Majority (93.2%) presented with stressful life events. Common stressful life events were changing eating habit (25.2%), change in sleeping habit (20.8%) and financial loss or problem (18.8%). Conclusion: Many people remain troubled by symptoms for long term. So, proper psychiatric evaluation is necessary for successful alleviation of the bothering symptoms of such incurable functional illness. KYAMC Journal. 2022;12(04): 200-204